2022
DOI: 10.1002/brb3.2533
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics and prognostic factors in 110 patients with nitrous oxide abuse

Abstract: Purpose: To review the clinical symptoms, auxiliary examination findings, and outcomes of patients with nitrous oxide (N 2 O) abuse, and analyze the factors that affect outcomes. Methods: Patients with N 2 O abuse treated in the Department of Neurology between January 2018 and December 2020 were included. The clinical data of these patients were collected, and follow-up was conducted to determine the outcomes. Results: The average age of the 110 patients with N 2 O abuse was 21.4 ± 4.2 years (range: 14-33 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 60 publications
5
32
0
11
Order By: Relevance
“…These patients primarily exhibited limb numbness or weakness, especially the lower limbs. Decreased muscle strength, superficial sensory disturbances, and decreased tendon reflex were the most common neurological signs according to the published report (7). Increased plasma homocysteine level is more sensitive than plasma vitamin B12 level for clinical diagnosis, as N 2 O mainly consumes vitamin B12 in tissue but not blood (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients primarily exhibited limb numbness or weakness, especially the lower limbs. Decreased muscle strength, superficial sensory disturbances, and decreased tendon reflex were the most common neurological signs according to the published report (7). Increased plasma homocysteine level is more sensitive than plasma vitamin B12 level for clinical diagnosis, as N 2 O mainly consumes vitamin B12 in tissue but not blood (3).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral neuropathy is the most common N 2 O-related neurological disorder with a morbidity up to 97% ( 7 ). These patients primarily exhibited limb numbness or weakness, especially the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Lystgassindusert nevropati beskrives typisk hos unge mennesker i 20-årene og rammer i bemerkelsesverdig grad mest underekstremitetene, med symptomer som inkluderer varierende grad av ustøhet, nummenhet og svakhet (11,12). Nevrofysiologisk beskrives oftest en sensorimotorisk nevropati med blandet aksonal og demyeliniserende affeksjon.…”
Section: Diskusjonunclassified
“…A Dutch study in patients intoxicated with N 2 O reported that 38% of the patients showed signs of neuropathy [1]. The literature showed that 36–98% of patients who presented in the hospital with N 2 O abuse showed signs of neuropathy [16, 17]. Supplementation with vitamin B12 could reverse damage, provided that N 2 O use is discontinued [18, 19].…”
Section: Introductionmentioning
confidence: 99%